The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/fst.105921
|View full text |Cite
|
Sign up to set email alerts
|

Animal feed based on forage cactus: use of viscera in traditional dishes. Production of by-products that can result in an economic return

Abstract: The study aimed to evaluate the yield of components that are not part of the carcass, edible organs, and with a commercial value of sheep finished in feedlot fed with complete ration silage based on forage cactus and different levels of inclusion of cotton cake. Thirty-two crossbred Dorper lambs with Santa Inês hairless sheep were used, with an initial age of 120 days, weighing on average 17 ± 1.5 kg. Consumption of 5% of the live weight of dry matter was established, being weighed and readjusted daily accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…When comparing rations with AM and SO in relation to blood metabolites (table 3), it was observed that AM (P<0.05) increased in almost 15 mg.dL -1 the amount of glucose in blood compared to the control diet and the amount of globulin of the AM diet (4.12) increased 0.67 g.dL -1 compared to the SO (3.45), in addition, creatinine (1.09) and TGO (63.86) decreased compared to the SO diet (1.45 and 91.57, respectively); the inclusion of AM compared to SO decreased cholesterol, triglycerides, VLDL and R A/G, which could be a tendency in the modification of these variables by the inclusion of AM (P<0.10). The increase in blood glucose due to the inclusion AM reflects a greater disposition of energy, associated to a greater production of propionic acid available for muscle production, as reported by de Castro et al (2023) and Rodrigues et al (2022).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…When comparing rations with AM and SO in relation to blood metabolites (table 3), it was observed that AM (P<0.05) increased in almost 15 mg.dL -1 the amount of glucose in blood compared to the control diet and the amount of globulin of the AM diet (4.12) increased 0.67 g.dL -1 compared to the SO (3.45), in addition, creatinine (1.09) and TGO (63.86) decreased compared to the SO diet (1.45 and 91.57, respectively); the inclusion of AM compared to SO decreased cholesterol, triglycerides, VLDL and R A/G, which could be a tendency in the modification of these variables by the inclusion of AM (P<0.10). The increase in blood glucose due to the inclusion AM reflects a greater disposition of energy, associated to a greater production of propionic acid available for muscle production, as reported by de Castro et al (2023) and Rodrigues et al (2022).…”
Section: Resultssupporting
confidence: 56%
“…In this sense Yue et al (2016), mention that the expression of lipogenic genes is involved for the increase of fatty acid desaturation, which is associated with the increase of MUFA by SFA. An association such as glucose with the FASBP3 gene could mean a greater development of muscle tissue according to Castro et al (2023) andRodrigues et al, (2022).…”
Section: Resultsmentioning
confidence: 98%
“…This might have been reflected in glucose concentrations, which were higher in control diets. Another possibility is related to a probable increase in propionic acid in the rumen or glycogenic amino acids in the diet, as ruminants are neoglucogenic animals (41), and the volume of glucose in the blood is almost equivalent to the production of propionate in the rumen, which in turn is regulated by the energy source in the diet (42, 43); however, the results found are within the reference values. The increase in serum concentrations of cholesterol, triglycerides, and HDL was the result of increased lipid absorption in the intestine and increased metabolites in the bloodstream, due to the fat content of the CUP, TUC, and C80 diets.…”
Section: Concentration Of Serum Metabolitesmentioning
confidence: 99%